D1–D2 dopamine receptor heterooligomers with unique pharmacology are coupled to rapid activation of G(q)/11 in the striatum - Rashid, Asim J. (National Academy of Sciences, 2007)
We demonstrate a heteromeric D1–D2 dopamine receptor signaling complex in brain that is coupled to G(q)/11 and requires agonist binding to both receptors for G protein activation and intracellular calcium release. The D1 agonist SKF83959 was identified as a specific agonist for the heteromer that activated G(q)/11 by functioning as a full agonist for the D1 receptor and a high-affinity partial agonist for a pertussis toxin-resistant D2 receptor within the complex. We provide evidence that the D1–D2 signaling complex can be more readily detected in mice that are 8 months in age compared with animals that are 3 months old, suggesting that calcium signaling through the D1–D2 dopamine receptor complex is relevant for function in the postadolescent brain. Activation of G(q)/11 through the heteromer increases levels of calcium/calmodulin-dependent protein kinase IIα in the nucleus accumbens, unlike activation of G(s)/olf-coupled D1 receptors, indicating a mechanism by which D1–D2 dopamine receptor complexes may contribute to synaptic plasticity.